DEVELOPING RELATIONSHIP OF TEACHERS AND STUDENTS THROUGH SNAP DIARY AS A CHILDREN'S FRIENDLY SCHOOL SUPPORT IN ELEMENTARY SCHOOL - Utami, Wulan Tri Puji (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
Education really aims to humanize humans. When a childborn into the world, he is equipped with various potential that must be actualized. The process of actualization is done deliberately called the educational process. The teacher plays an important role in the processeducation primarily in shaping a child's ability to shape skillsin the form of cognitive, affective and psychomotor. Teachers are also influential to make improvements to a healthy learning environment, conducive and comfortable for students. Complete school facilities are certainly not a guarantee for the protection of children's rights because violence in primary school-aged children is still common in schools. Implementation of child-friendly school program is done to reduce the problem to the students according to rights in convention of child. One of the main pillars of child-friendly school is the availability of a healthy, safe and protective environment. Schools also serve to protect children's rights so that children feel safe from violence, abuse and exploitation. While it is easy to understand that a nonviolent environment is a prerequisite of productive learning, it is certainly more difficult to take precautions. Improving the relationship of teachers and students to be one strategic action to understand the needs of each student. Effective communication relationship can be done through snap diary program. Every student has right and freedom to talk about the events that he has experienced. Through a snap diary, students can express the events they experienced not only through writing but also through pictures. Teacherwhich has a large number of classes will be easier to analyze the problems of students through snap dairy.